Optimizing Sulfuric Acid 98% Leaching: Lithium Recovery from Madagascar Spodumene - Rija, Rabearisoa Solotiana; Baholy, Robijaona Rahelivololoniaina (Budapest International Research and Critics University, 2025)
A comprehensive study of lithium extraction from Vakinankaratra, Madagascar spodumene through sulfuric acid digestion and subsequent aqueous leaching is presented. The process initiates with calcination, a pretreatment designed to induce the alpha-to-beta phase transformation of spodumene, resulting in decreased density, increased friability, and enhanced chemical reactivity. Characterization of the ore, employing X-ray fluorescence (XRF) and atomic absorption spectroscopy (AAS), revealed a mineralogical composition dominated by oxides of lithium, silicon, aluminum, potassium, and fluorine, confirming the presence of economically relevant lithium concentrations. The investigation explored the influence of reaction time, varying from one to three hours, at elevated digestion temperatures. Rigorous optimization of experimental parameters was conducted, yielding significant insights into the leaching process. The findings demonstrate a strong correlation between lithium extraction efficiency and the ore-to-acid ratio, temperature, and, most notably, reaction time. Under optimized conditions, specifically a reaction temperature of 250°C and a duration of three hours, a 92% lithium extraction rate was achieved for both calcined spodumene and lepidolite samples. This study provides a detailed understanding of the critical parameters governing lithium extraction from Malagasy spodumene, contributing to the development of efficient and industrially applicable extraction methodologies.